Evaluation of intrapleural fibrinolytic therapy and dosing strategies used for complicated pleural effusions. (October 2022) - Baumgartner, Laura; Huang, Eric; Sherman, Deborah
Abstract: Objectives: Compare the use of Tissue Plasminogen Activator (t-PA) and t-PA + Dornase (DNase) for the management of complicated pleural effusions, and to determine if a dose-response relationship exists for t-PA. Methods: Retrospective cohort study that examined all adult patients at a large academic medical center who received intrapleural t-PA or t-PA + DNase for the management of a complicated pleural effusions. Outcomes were success of therapy [defined as avoidance of secondary interventions (i.e. VATSD or thoracotomy)], chest tube output pre- and post-administration, radiographic findings, t-PA dose and frequency, and bleeding complications. Results: Thirty-five patients were enrolled: 25 received t-PA and 10 received t-PA + DNase. Successful pharmacologic treatment occurred in 88% of patients receiving t-PA and 100% of patients receiving t-PA + DNase (p = 0.54). In the t-PA group, chest tube output increased from 75 ml/12 h to 538 ml/12 h after administration of t-PA (p = 0.001), and from 103 ml/12 h to 502 ml/12 h (p = 0.001) in the t-PA + DNase group. Radiographic improvement occurred in 84% of t-PA patients and 90% of t-PA + DNase patients (p = 0.99). In the t-PA group, a successful response occurred in 92% of patients receiving a cumulative dose of ≤10 mg (n = 13) and 83% of patients receiving a cumulative dose of >10 mg (n = 12), p = 0.43. Patients who received a single t-PA dose compared to those who received multiple doses also had similar success rates (p = 1). There was one instance of bleeding following drug administration. Conclusion: Both t-PA and t-PA + DNase were highly effective for reducing a patient's need for surgical intervention. Higher cumulative doses or more frequency administrations did not appear to provide additional benefit.